(untitled) (Margalla Papers, 2024)
India’s strategic behaviour in the Indian Ocean is important, given its geographic location, economic and military power expansion, and growing regional footprint. The Indian Ocean, a critical conduit for trade and energy, with major sea lanes passing through it, is significantly influenced by India’s strategic behaviour and intentions. The mounting sea-based nuclear forces, as a crucial and survivable component of nuclear deterrence, have also emerged as a concern for assessing the state of a credible second-strike platform. Therefore, the significance of naval nuclear forces has stimulated a continual, global focus shift from land to the seas. In this context, South Asia has also developed this major component of national power in the last few decades. This paper discusses the main features of ongoing naval build-up in India and Pakistan, the motivations and aspirations of both India and Pakistan and the ongoing debate on naval nuclear-capable developments in the Indian Ocean region. Also, how will naval nuclear developments be assessed for escalation risk and crisis stability in the maritime domain? The implications of India's naval build-up for the regional strategic environment are profound, influencing neighbouring states' and external stakeholders' policies and actions. Bibliography Entry Rehman, Huma. 2024. "India’s Growing Strategic Behaviour in the Indian Ocean: Implications for Regional Strategic Environment." Margalla Papers 28 (1): 30-44.